PELATIHAN PENDIDIKAN PARENTING BAGI ORANG TUA SISWA PADA MASA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH NEGERI 2 SAMBAS - Purniadi Putra; Arnadi; Hadisa Putri (Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service is one of the manifestations of the Tri Dharma Higher Education activities that must be carried out by all lecturers at universities, including in this case the Sultan Muhammad Syafiuddin Sambas Islamic Institute as one of the Islamic Higher Education institutes in the Indonesia-Malaysia border area. Community service and empowerment activities are by providing parenting education training for parents of students during the Covid-19 Pandemic at Madrasah Ibtidaiyah Negeri 2 Sambas. The purpose of this parenting education training is to train parents of students in understanding the importance of parenting and their involvement in the child's learning process comprehensively. The purpose of the research is to provide enlightenment and learning models for Covid-19. To overcome the problems that occur, it is very necessary to hold intensive guidance for family education at home and teachers to provide intensive guidance in parenting education training during the current Covid-19 Pandemic. The implications of family education guidance will provide parents with knowledge at home and at school, especially in Madrasah Ibtidaiyah Negeri 2 Sambas. The result of this research is that the implementation of the training is carried out through direct training and practice. The method used is the lecture method, discussion, and sharing of experiences during the event. The results show the satisfaction of the participants in the training and understand the importance of parenting education assistance during the COVID-19 pandemic in the very good category.